Development of visible light-responsive mono and codoped TiO2 for photocatalytic degradation of methyl orange dye - Malik, Z.; Ibrahim, S.A.; Ainuddin, A.R.; Hussin, R.; Kamdi, Z. (2024)
Titanium dioxide (TiO2) has been acknowledged as a promising photocatalyst in environmental remediation including wastewater treatment. In this study, TiO2 nanoparticles either by single or co-doped of iron (Fe) and nitrogen (N) via sol-gel method and calcined at 500 °C for 3 hours. This experiment investigated the performance of mono/co-dopant of TiO2 photocatalyst against methyl orange in aqueous solution under UV light irradiation. The experimental results showed the rate of degradation favored in co-doped TiO2 followed by mono doped TiO2 and pristine TiO2. The photocatalytic reaction followed pseudo first-order kinetics which were rationalized in terms of the Langmuir– Hinshelwood model and provided nearly complete degradation